2022
DOI: 10.1007/s00520-022-07239-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional prehabilitation in head and neck cancer: a systematic review

Abstract: Purpose: Prehabilitation affords an opportunity to support the management of malnutrition that is strongly associated with head and neck cancer. The purpose of this systematic review was to identify the components of nutritional prehabilitation interventions and their effects on nutritional and health outcomes in head and neck cancer patients. Methods: A comprehensive search was completed within Medline (including PubMed), CINHAL, Cochrane database, EMBASE, PRoQUEST, clinical trials registries and grey literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Pre-emptive management of treatment side effects, such as mucositis, nausea and dysphagia, should be prioritised, particularly in vulnerable groups. Nutritional prehabilitation delivered before and during treatment may help to prevent deterioration, although evidence to support its effectiveness in HNC is lacking [ 25 ]. Regional data is also important in order to appropriately consent patients when discussing treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-emptive management of treatment side effects, such as mucositis, nausea and dysphagia, should be prioritised, particularly in vulnerable groups. Nutritional prehabilitation delivered before and during treatment may help to prevent deterioration, although evidence to support its effectiveness in HNC is lacking [ 25 ]. Regional data is also important in order to appropriately consent patients when discussing treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction and use of prehabilitation could also help achieve long-term MNT in patients with HNC. This would allow for the identification of patients at risk before surgery and other anti-cancer treatments and the early introduction of MNT, thus prolonging the time to therapy [29][30][31][32]. Prehabilitation could also allow for intervention before the signs of malnutrition are present and prevent deterioration in nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…These pre-operative interventions alongside other multimodal and multidisciplinary approaches to optimize patient’s physical, nutritional and mental status prior to surgery has been termed prehabilitation and can also include exercise programs and dysphagia rehabilitation [ 35 , 36 ]. A systematic review of nutrition interventions undertaken in the HNC prehabilitation setting identified only two studies which examined the use of an enriched formula versus standard nutrition support in malnourished patients and found no additional benefit of the enriched formula in mitigating weight loss [ 37 ]. The authors concluded, however, that due to the malnutrition risks on diagnosis and the negative impact of poor nutritional status on clinical outcomes, further robust nutritional prehabilitation research is required to inform clinical practice.…”
Section: Discussionmentioning
confidence: 99%